Desarrollo de un Sistema de Gestión de Aprendizaje como herramienta que permita organizar, centralizar contenidos académicos y facilitar la exposición de recursos formativos - Ramírez Coronel, Edison Enrique (2023)
In this changing world, there are more and more students who cannot attend classes due to work, family responsibilities, distance or the expenses that traditional education entails. Against this, learning management systems are increasingly popular in the educational field due to its wide range of functionalities and advantages. These systems combine pedagogical elements and teaching models to provide students with a modern and effective learning tool. Faced with this, the current degree work proposes the development of a Learning Management System as a tool that allowed organizing and centralizing academic content to facilitate the exposure of training resources. In this software development process, the ICONIX methodology was used because it is iterative and incremental, focusing on the construction of functional prototypes and the early validation of requirements, dividing the process into four phases: Requirements, Design, Implementation and Testing. As a final result, a system was developed that allowed the centralization and management of the teaching-learning process, allowing the administration of all educational resources in one place, facilitating their management and organization. This tool allowed more precise and continuous monitoring of student progress, which facilitates the early identification of needs and the implementation of improvement strategies. The validation of the progress in the training of teaching resources, as well as the evaluation of the different components was important when recognizing the strengths and weaknesses of the participants, this was achieved thanks to the monitoring and study of metrics related to the progress of each participant. Keywords: knowledge management, educational platform, online platform, LMS, learning, virtual classroom.